Dampak Penerapan Sertifikasi Indonesia Sustanable Palm Oil (ISPO) Terhadap Petani Anggota Koperasi (Studi Kasus: Koperasi Sekato Jaya Lestari Kabupaten Siak, Riau) - Asti, Nurul Fitri; Dewi, Novia; Yusri, Jum’atri (Universitas Galuh, 2025)
In order to create sustainable and enduring palm oil plantation management and to fulfill the commitment to achieve and support responsible palm oil plantations and management, the Indonesian government has formulated a policy called Indonesian Sustainable Palm Oil. (ISPO). This research aims to identify the factors influencing cooperatives in obtaining the ISPO certificate and to analyze the impact of differences in price, sales volume, production costs, and income on cooperative member farmers before and after obtaining the Indonesia Sustainable Palm Oil certificate. (ISPO). The research location is in Mandiangin Village, Minas District, Siak Regency, Riau Province. The research method used is the case study method. The location determination technique uses the purposive method, meaning the area chosen for the research is intentional. The sampling method uses the Purposive Sampling technique and requires key informants. The data collection method includes primary data obtained directly from the Sekato Jaya Lestari Cooperative and secondary data obtained from the cooperative's treasurer and secretary, as well as other related parties. The data analysis methods used in this study are descriptive and Compare Means Paired Sample t-test. (Uji beda rata – rata berpasangan). The research results indicate that the factors influencing cooperatives in obtaining the Indonesia Sustainable Palm Oil (ISPO) certification are regulations, the environment, and financing institutions. Furthermore, the research findings show that the members of the Sekato Jaya Cooperative experienced a price increase of 17.59% after obtaining the ISPO certification, a sales volume increase of 110,815 tons, production costs rose due to cultivation activities to meet ISPO standards, and the income of the Sekato Jaya Lestari Cooperative farmers increased after obtaining the ISPO certification.